Effects of varying sorghum grain soybean meal ratios and added methionine on swine gains, feed efficiency and carcass composition and quality - Kropf, Donald H.; Kasten, L.H.; Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Limited work is available on proper protein levels in swine rations when sorghum grain is a major ration component. Remarkable improvement has been made in gaining ability, feed coversion and muscling in swine. Because of continued improvements in these characteristics due to breeding and selection, we need to periodically re-evaluate the requirements for protein and amino acid levels in swine rations. A deterioration in muscle quality' (color, firmness and marbling) seems to be associated with production of lean pork. This prompted a detailed study of muscle quality, carcass composition, feed/gain ratio and gain rate as affected by varying ratios of sorghum grain and soybean meal, as well as added methionine, in swine rations.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; Sorghum grain; Soybean meal; Methionine; Carcass composition